Effects of turmeric extract on hemin-induced low-density lipoprotein oxidation - Prapaporn Chaniad (2019)
© 2018 Wiley Periodicals, Inc. Hemin is an oxidative mediator elevated in disease states including sickle cell anemia and thalassemia. The rhizome of Curcuma longa L. contains yellow pigments called curcuminoids which have antioxidant and anti-inflammatory activities. The aim of the study was to compare the protective effects of curcuminoids, curcumin, demethoxycurcumin, bisdemethoxycurcumin, and tetrahydrocurcumin on hemin-induced LDL oxidation (he-oxLDL). He-oxLDL showed the depletion of α-tocopherol, an increase in thiobarbituric acid reactive substances (TBARs), and alteration of the lipid composition in low-density lipoprotein. The levels of cholesteryl arachidonate, cholesteryl linoleate and the cholesteryl linoleate/cholesteryl oleate ratio were decreased. All test compounds showed antioxidant activity that protected against hemin-induced lipid peroxidation, based on the inhibition of TBARs formation, reduced depletion of α-tocopherol, decreased damage to lipids, and a reduced decrease in the cholesteryl linoleate/cholesteryl oleate ratio. A significant protective effect against he-oxLDL was found to be tetrahydrocurcumin ≥ curcumin ≥ curcuminoids > demethoxycurcumin ≥ bisdemethoxycurcumin ≥ α-tocopherol (p <.05). Practical applications: Curcuma longa L. has traditionally been used in Ayurvedic medicine for treatment of conditions such as arthritis, ulcer, jaundice, wounds, and skin diseases. It has also been used as a food additive. The results from this study demonstrated that curcuminoids derived from the rhizome of Curcuma longa L. are the potential substances for protecting hemin-induced LDL oxidation which may be developed as a functional food for the prevention of diseases related to low-density lipoprotein oxidation.